2007
DOI: 10.1111/j.1365-2929.2006.02669.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical e-learning: validation of multimedia web-based lectures

Abstract: The addition of aural files to the novel web-based lecture series is face valid and results in significantly increased examination performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 8 publications
3
46
0
7
Order By: Relevance
“…23,24 Many orthopedic programs train with cadavers, which are not standardized, require dedicated space, cost, supply, and legal issues. 17 E-learning platforms are flexible, standardized, archived, reused, and free the institution from the costly specialized facilities necessary to house a cadaver-based program to prepare residents for operating room.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Many orthopedic programs train with cadavers, which are not standardized, require dedicated space, cost, supply, and legal issues. 17 E-learning platforms are flexible, standardized, archived, reused, and free the institution from the costly specialized facilities necessary to house a cadaver-based program to prepare residents for operating room.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of incorporating audiovisual elements to an educational instruction to enhance learning are well recognized with an increase org/10.15694/mep.2017.000084 in knowledge retention and technical proficiency (Collins et al, 2015) , (Mehrabi et al, 2000) , (Ridgway et al, 2007). Audiovisual instruction provides a mental standard to which trainees can compare their performance (Custers, Regehr, McCulloch, Peniston, & Reznick, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32]. Finally, multiple studies demonstrated that knowledge was equivalent (or better) between students learning through online lectures compared to traditional learning modalities, such as live didactic lectures [8,9,12,19,22,23,25,28,[33][34][35][36][37][38], with the exception of one study that found superior student knowledge acquisition from live lectures [39].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%
“…Regardless of the method of assessment, almost all studies reported high satisfaction and increased knowledge after intervention. Student self-assessment typically revealed positive attitudes toward online lectures as a teaching modality [7,8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%